2010
DOI: 10.1073/pnas.1000001107
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast solvation dynamics at binding and active sites of photolyases

Abstract: Dynamic solvation at binding and active sites is critical to protein recognition and enzyme catalysis. We report here the complete characterization of ultrafast solvation dynamics at the recognition site of photoantenna molecule and at the active site of cofactor/ substrate in enzyme photolyase by examining femtosecondresolved fluorescence dynamics and the entire emission spectra. With direct use of intrinsic antenna and cofactor chromophores, we observed the local environment relaxation on the time scales fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 47 publications
6
89
0
Order By: Relevance
“…These dynamics usually follow a stretched-exponential decay behavior, reflecting heterogeneous ET dynamics controlled by the active-site solvation (5,6,11). However, in that study, no thymine-related species could be detected in the visible-light region and no information about the dimer splitting was obtained.…”
mentioning
confidence: 54%
“…These dynamics usually follow a stretched-exponential decay behavior, reflecting heterogeneous ET dynamics controlled by the active-site solvation (5,6,11). However, in that study, no thymine-related species could be detected in the visible-light region and no information about the dimer splitting was obtained.…”
mentioning
confidence: 54%
“…2a and Supplementary Fig. 1a), Ae À ðt=tÞ b (A, amplitude; t, decay time constant; and b, stretched parameter), due to the modulation of ET by active-site solvation on similar timescales [11][12][13]19,20 . Using t h i ¼ ðt=bÞGð1=bÞ and knowing the deactivation lifetimes (t LT ) in nanoseconds in the absence of substrate (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have to emphasize that the ET reactions are coupled with active-site relaxation. We have measured the active-site solvation dynamics in the reduced FADH -state and have found that the relaxation takes place on the timescales from a few picoseconds to subnanoseconds (21). The similar timescales would be expected for the oxidized FAD state (22) and therefore the ET dynamics shows a stretched behavior, Ae −ðt=τÞ β , where A is the amplitude, τ is the lifetime, and β here is a stretched parameter.…”
Section: Identifying New Electron Donors (Ade and W384) In Initial Elmentioning
confidence: 96%
“…The derived ET values of free energies and reorganization energies from Eq. 1 are under assumption of equilibrium ET processes, and clearly these ET dynamics reported here are in nonequilibrium with local protein and solvent relaxations due to the overlap of timescales between ET dynamics and active-site relaxation (21). Woiczikowski et al (32) recently reported nonadiabatic quantum mechanics/molecular mechanics simulations of these ET dynamics and also showed the nonequilibrium nature of these tunneling processes.…”
Section: Characterizing Terminal Electron Donor (W306) and Completingmentioning
confidence: 99%